Anna K. Dulska. Malitia temporis? Personas, gobierno y entorno de la Orden de San Juan de Jerusalén en Navarra medieval. New York: Peter Lang, 2021. 306 Seiten, 13+12 Abb., 7 Tab. ISBN 978-14-33170-05-8. - Jaspert, Nikolas (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2025)